Prevalence of pathogenic Klebsiella pneumoniae based on PCR capsular typing harbouring carbapenemases encoding genes in Uganda tertiary hospitals - Ssekatawa, Kenneth; Byarugaba, Denis K.; Nakavuma, Jesca L.; Kato, Charles D.; Ejobi, Francis; Tweyongyere, Robert; Wampande, Eddie M. (Antimicrobial Resistance & Infection Control, 2021)
Background: Klebsiella pneumoniae is an opportunistic pathogen that has been implicated as one of commonest cause of hospital and community acquired infections. The K. pneumoniae infections have considerably contributed to morbidity and mortality in patients with protracted ailments. The capacity of K. pneumoniae to cause diseases depends on the presence of an array virulence factors. Coexistence and expression of virulence factors and genetic determinants of antibiotic resistance complicates treatment outcomes. Thus, emergence of pathogenic MDR K. pneumoniae poses a great threat to the healthcare system. However, the carriage of antibiotic resistance among pathogenic K. pneumoniae is yet to be investigated in Uganda. We sought to investigate the carbapenem resistance profiles and pathogenic potential based on capsular serotypes of K. pneumoniae clinical isolates. Methods: This was a cross sectional study involving use of archived Klebsiella pneumoniae isolates collected between January and December, 2019 at four tertiary hospitals in Uganda. All isolates were subject to antimicrobial susceptibility assays to determine phenotypic antibiotic resistance, pentaplex PCR to detect carbapenemases encoding genes and heptaplex PCR to identify capsular serotypes K1, K2, K3, K5, K20, K54 and K57. Results: The study found an overall phenotypic carbapenem resistance of 23.3% (53/227) and significantly higher genotypic resistance prevalence of 43.1% (98/227). Over all, the most prevalent gene was blaOXA-48-like (36.4%), followed by blaIMP-type (19.4%), blaVIM-type (17.1%), blaKPC-type (14.0%) and blaNDM-type (13.2%). blaVIM-type and blaOXA-48-like conferred phenotypic resistance in all isolates and 38.3% of isolates that harbored them respectively. Capsular multiplex PCR revealed that 46.7% (106/227) isolates were pathogenic and the predominantly prevalent pathotype was K5 (18.5%) followed by K20 (15.1%), K3 (7.1%), K2 (3.1%) and K1 (2.2%). Of the 106 capsular serotypes, 37 expressed phenotypic resistance; thus, 37 of the 53 carbapenem resistant K. pneumoniae were pathogenic. Conclusion: The high prevalence of virulent and antibiotic resistant K. pneumoniae among clinical isolates obtained from the four tertiary hospital as revealed by this study pose a great threat to healthcare. Our findings underline the epidemiological and public health risks and implications of this pathogen.
Keywords: Carbapenem resistance; Klebsiella pneumoniae PCR capsular typing; Virulent factors